Influence of wood moisture content on the modulus of elasticity in compression parallel to the grain - Diogo Aparecido Lopes Silva; Francisco Antonio Rocco Lahr; Obede Borges de Faria; Eduardo Chahud (Materials Research, 2012)
Brazilian Standard ABNT NBR7190:1997 for timber structures design, adopts a first degree equation to describe the influence of wood moisture content. Periodically, when necessary, the referred standard is revised in order to analyze inconsistencies and to adopt considerations according new realities verified. So, the present paper aims to examine the adequacy of its equation which corrects to 12% of moisture the values of rigidity properties obtained on experimental tests. To quantify the moisture influence on modulus of elasticity, it was applied tests of compression parallel to the grain for six specimens of different strength classes, considering nominal moisture of 12; 20; 25; 30%. As results, modulus of elasticity in the moisture range 25-30% showed statistically equivalents, and was obtained a first degree equation to correlate the studied variables which leads to statically equivalent estimations when compared with results by ABNT NBR7190:1997 equation. However, it was indicated to maintain the current expression for the next text of the referred document review, without prejudice to statistical significance of the estimates.